The Animal – The Anthropic – The Automaton : Farming and Technology in Icelandic Agriculture - Guðný Sara Birgisdóttir 1993- (2020)
This research explores current automatization in agriculture on a local, Icelandic scale compared to the global one. It sheds light on the future of the topic in the context of old traditions, food production, future foods, and concepts such as techno-pessimism, techno-optimism, appropriate technologies and precision agriculture. The research is based upon interviews conducted by the author in Iceland over a few months, books and articles on the matter, and a critical discussion of designers, artists, and authors who focus on technology in agriculture. This thesis does not pretend to define the best possible future for technology in agriculture. It should instead show various points of view regarding specific topics, for example, farmbots and the prevention of animal disease. The thesis also draws attention to the factors influencing farmers´ choice of technology, such as the lack of governmental financial support. It seems to make the farmer´s society unable to change its production or test innovative ideas or new technology to keep its practice afloat. It is essential, or else farmers will be forced to find different types of work, often in the cities, causing depopulation in the rural, already fragile, areas of the Icelandic countryside. Traditional methods are getting replaced by new technology globally, bringing exciting possibilities to the agricultural scene in Iceland and providing more sustainable ways of horticulture. We need to figure out ways to hold on to both science and nature and see how agricultural innovation can have an equivalent value to progress. Therefore, it should be entitled to sufficient financial support to aggrandize rural areas, and the increasing want or need for connection with nature.